TPACK Skills of Pre-service Teachers in Technology Integration: A Study in Microteaching Class - Firmanti, Pipit; Yuberta, Fauzi; Purnomo, Yoppy Wahyu; Firdaus, Fery Muhamad (Southeast Asian Mathematics Education Journal, 2024)
The integration of technology in mathematics education is a tangible manifestation of the rapid development of the times. Therefore, teachers must use technological devices to ensure students stay competitive in the global arena. This study aims to describe the distribution of TPACK skills among pre-service mathematics teachers and monitor their development during their microteaching experiences. This research is a qualitative descriptive study. The participants in the study were eleven students at UIN Sjech M Djamil Djambek Bukittinggi who were taking a microteaching course in the even semester of 2023/2024. The instruments used were the TPACK questionnaire and observation sheets. Based on the observation, in the first session, some subjects were unable to use or operate the software they had downloaded, and many quiz applications encountered problems because they could not be opened. The challenges faced included paid software and issues operating the software on different laptops. It is suspected that one student did not attend because she was not prepared to present. Additionally, the development of skills for each TPACK aspect generally showed improvement in subsequent sessions. The subjects generally used presentation slide applications such as Microsoft PowerPointTM and CanvaTM to explain the material and conducted evaluations by giving quizzes through applications such as QuizizzTM, KahootTM, WordwallTM, and BamboozleTM. The results show that the students' skills based on the TPACK Questionnare were at a moderate level with an average score of 3.38. However, there are differences between the results of the questionnaire and the observations carried out. For instance, in the aspect of Technological Pedagogical Knowledge especially for item "I can utilize available technologies as a learning aid". The questionnaire showed a high rating 3.63. On the other hand, observations indicate that students' abilities are still lacking, indicating that students have much to learn, especially in the use of technology in the learning process to enhance the learning environment in mathematics.